Association of dietary inflammatory index and oxidative balance score with all-cause and cardiovascular mortality in US non-diabetic adults - YuNan Han; Lin Li; YongXiang Wang; Wen Fan (Frontiers in Nutrition)
BackgroundInflammation and oxidative stress (OS) are critical factors in the pathogenesis of chronic diseases (CDs), with dietary factors being a central modifiable determinant. This study aimed to assess the association of the Dietary Inflammation Index (DII) and Dietary Oxidative Balance Score (DOBS) with all-cause and cardiovascular (CV) mortality in non-diabetic adults.MethodsData on non-diabetic adults were extracted from the National Health and Nutrition Examination Survey (NHANES) (2009–2018). Dietary information was collected via 24-h recalls, and DII and DOBS were calculated. Multivariate weighted Cox proportional hazards models, Kaplan–Meier (KM) survival analysis, and restricted cubic spline (RCS) analyses were conducted to assess mortality associations. Subgroup analyses were performed based on gender, age, BMI, smoking status, hypertension, and hyperlipidemia.ResultsAfter applying multivariable–weighted Cox proportional hazards regression, participants with the highest DII quartile exhibited elevated risks of all-cause mortality [Q4: HR = 1.554 (1.258, 1.934)] and CV mortality [Q4: HR = 2.100 (1.307, 3.375)]. In contrast, the highest DOBS quartile was linked to reduced all-cause mortality [Q4: HR = 0.724 (0.553, 0.946)], with no significant association observed for CV mortality. RCS analyses confirmed a positive dose–response between DII and both mortality outcomes, as well as an inverse relationship for DOBS. Subgroup analyses revealed that high DOBS (Q4) scores were negatively associated with all-cause and CV mortality in women, individuals aged ≥60 years, current smokers, hypertensive individuals, and those without dyslipidemia. High DII (Q4) scores were positively associated with all-cause mortality across all sexes, individuals aged ≥60 years, smokers, and those with hypertension or dyslipidemia. Additionally, high DII scores were associated with CV mortality among women, both smokers and non-smokers, and individuals without hypertension or dyslipidemia.ConclusionHigher DOBS levels are associated with lower all-cause mortality, while higher DII levels are linked to increased all-cause and CV mortality. Dietary interventions targeting inflammation may reduce mortality risks, thereby informing public health strategies.